Karakteristik Batuan Pra-Tersier dan Tersier Berdasarkan Metode Petrografi Studi Kasus pada Daerah Muaro Sijunjung, dan Sekitarnya, Kabupaten Sijunjung, Sumatera Barat - Radiyan Nur Iksan; Harnani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Muaro Sijunjung area and its surroundings, Sijunjung Regency, West Sumatra, have complex geological conditions due to the influence of tectonic, magmatic, and sedimentary processes that have occurred from the Pre-Tertiary to the Tertiary periods. This study aims to identify the characteristics of Pre-Tertiary and Tertiary rocks based on petrographic analysis to understand their mineralogical composition, texture, and formation processes. The research method involved petrographic observation of thin sections using a polarizing microscope with parallel and crossed nicols. The analyzed samples were sourced from the Kuantan Formation (Pckl), Granite Intrusion (Tgr), Sawahtambang Formation (Tost), and Ombilin Formation (Tmo). Analysis results indicate that the Kuantan Formation consists of crystalline limestone classified as Dismicrite Mudstone, while the Granite Intrusion comprises Monzo-Granite and Syeno-Granite. The Sawahtambang Formation is dominated by non-carbonate sandstone classified as Sublitharenite Arkose, while the Ombilin Formation consists of carbonate sandstone and carbonate mudstone, classified as Lithic Wacke and Mudrock, respectively. The observed mineralogical and textural characteristics indicate the influence of diagenetic, sedimentary, magmatic, and alteration processes on each rock unit. The research results indicate that the geological evolution of the Muaro Sijunjung area is controlled by the interaction of sedimentary processes, magmatic intrusions, and tectonic activity that occurred from the Pre-Tertiary to the Tertiary periods.